Provision of Public and Municipal Services to the Citizens of Saint-Petersburg Network of Multifunctional Centers - Vladimir Nikolaevich Naumov; Dmitry Viktorovich Kucherenko (Управленческое консультирование)
The article made a statistical analysis of the state and municipal services to the citizens of St. Petersburg multifunctional center.